PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, SALES GROWTH DAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN WHOLESALE AND RETAIL TRADE YANG TERDAFTAR DI BEI PERIODE 2012-2016 - CIPTAWAN . (LP2MTBM MAKARIOZ, 2018)
Information on the performance of the company is one of the important information and one type of information that into consideration investors in taking investment decisions. Company performance is generally assessed by comparison of the ratio of the fundamental elements within the company. This study aims to determine the effect of return on equity, debt to equity ratio, sales growth and dividends on stock prices on Wholesale And Retail Trade companies listed on the Indonesia Stock Exchange either partially or simultaneously. This research uses hypothesis test with descriptive quantitative by using multiple linear regression analysis. The results showed that partially debt to equity ratio and dividend affect the stock price while return on equity and sales growth does not affect the stock price in Wholesale And Retail Trade company listed on Indonesia Stock Exchange. Simultaneously, return on equity, debt to equity ratio, sales growth and dividend affect stock prices at Wholesale And Retail Trade companies listed on Indonesia Stock Exchange. Testing of coefficient of determination obtained value 0,436 means independent variable that is return on equity, debt to equity ratio, sales growth and dividend affect amount 43,6% to stock prices while 56,4% influenced by other variable like price earning ratio, earnings per share, net profit margin and so on.